Penerapan Strategi Marketing MIX Manisan Asam Gelugur dalam Upaya Peningkatan Target Pendapatan Desa Dogang - Ramadhani, Novitri; Nandani, Diajeng Regita; Hidayana, Nughrainy; Hendrawan, Yuda; Gustianda, Putra Rizky; Agustina, Reni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted with the aim of knowing about the marketing mix in an effort to increase revenue targets in the business of selling tamarind in the village of Dogang. This study uses a qualitative method with a type of method describing through previous research that is descriptive and objective in order to obtain a complete picture of something being studied. Marketing mix (marketing mix) is a combination or mixture of the entire marketing system where the variables that can be returned by the company to influence the reactions of potential customers. The main core of widely known marketing activities is the marketing mix, which includes the 4Ps (Product, Price, Place, Promotion). The four variables are a combination that has the same role and is a unit to support the company's success. Therefore product, price, place and promotion can be used by the company concerned to develop the company's basic strategy which can be used as a reference for the preparation of an effective marketing strategy. Keywords: Marketing mix strategy, Asam gelugur and revenue target